2004
DOI: 10.1177/002215540405200407
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-specific Expression of β-Carotene 15,15′-Mono-oxygenase in Human Tissues

Abstract: We studied the cell type-specific expression of human β-carotene 15,15′-mono-oxygenase (BCO1), an enzyme that catalyzes the first step in the conversion of dietary provitamin A carotenoids to vitamin A. Immunohistochemical analysis using two monoclonal antibodies against different epitopes of the protein revealed that BCO1 is expressed in epithelial cells in a variety of human tissues, including mucosa and glandular cells of stomach, small intestine, and colon, parenchymal cells in liver, cells that make up th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 36 publications
6
58
0
Order By: Relevance
“…In 2004 Lindquist and Andersson revealed that the normal endometrium expresses BCO1, the enzyme that catalyses the first step in the conversion of dietary provitamin A carotenoids to vitamin A. Thus it may be responsible for local synthesis of retinol from the carotenoids accumulated in the uterus in cases when their dietary supply is insufficient [26].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004 Lindquist and Andersson revealed that the normal endometrium expresses BCO1, the enzyme that catalyses the first step in the conversion of dietary provitamin A carotenoids to vitamin A. Thus it may be responsible for local synthesis of retinol from the carotenoids accumulated in the uterus in cases when their dietary supply is insufficient [26].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the bco1 and bco2 genes overlaps in the human gastrointestinal tract, but bco2, additionally, is expressed in several tissues neither known to be sensitive to vitamin A deficiency nor to express bco1 (20,21). The discovery that BCO1-null mice cannot metabolize b-carotene to vitamin A despite intact bco2 expression (22) implicated BCO2 in biological processes other than vitamin A synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…BCO2 is expressed in normal prostate epithelium (20,21). The observation that lycopene levels are significantly higher in cancerous than in normal or benign prostate (23) prompted our speculation that BCO2-mediated lycopene metabolism may be impaired in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some enter the blood associated with chylomicrons and both low-and high-density lipoproteins and are carried in the circulation to the tissues [Bendich and Olson, 1989;Lindqvist and Andersson, 2004]. Mammalian tissues, including human tissues, express both b-carotene-cleaving enzymes [Lindqvist and Andersson, 2004;von Lintig and Vogt, 2004;Lindqvist et al, 2005] suggesting that retinol synthesis can also occur locally at the tissue and organ level. Although both enzymes are expressed in many of the same tissues, significant differences exist.…”
Section: Discussionmentioning
confidence: 99%